Renewal of Archival Legacy Soil Data: A Case Study of the Busia Area, Kenya - Minai, Joshua O.; Schulze, Darrell G.; Libohova, Zamir (Frontiers in Soil Science, 2022)
Much older soils information, collectively known as legacy soil data lies idle in libraries or in the personal collections of retired soil scientists. The probability is very high for this legacy data to be lost or destroyed. We demonstrate the stepwise process of bringing legacy soils data ‘back to life’ using the Reconnaissance Soil Survey of the Busia Area (quarter degree sheet No. 101) in western Kenya as an example. The first step, site identification, involves meeting and deliberating with key institutions to identify a setting for the study. The second step, data archeology, involves locating and cataloging legacy soil data from key institutions, which often requires numerous site visits and the assistance of individuals familiar with the desired data. The third step, data rescue, involves converting paper copies of data into a digital format by scanning the maps, narrative descriptions, and tables, and storing the information in a database. The fourth step, data renewal, consists of bringing the data to modern standards by taking advantage of technological and conceptual advances in geoinformation technology. In our example, the resulting digital (scanned) soil map of the Busia Area is a significant upgrade from the fragile paper map. The fifth step, data interpretation, entails careful interpretation of the soil information available within the legacy soil survey to provide additional agronomic information. This allowed us to produce ten land quality maps showing the ability of the land to perform specific agronomic functions, and 18 different crop suitability maps that were not previously available. The rescued maps and their associated tabular and narrative data also provide crucial inputs for generating more detailed soil maps using digital soil mapping techniques that were unavailable when the original mapping was conducted.